PENGARUH KECAKAPAN TEKNOLOGI TERHADAP PRESTASI BELAJAR MAHASISWA - Astri Juwita Siregar; Nova Susanti; Isnaini Ramadhoniarti; Adinda Kurnia Komalasari; Gheriyah Rohima Nur Fatimah (Didaktika : Jurnal Kependidikan, 2022)
Since 2020, online learning has been implemented due to the covid-19 pandemic that has spread troughout Indonesia. So the learning can’t be carried out face-to face advance. Various educational institutions including University carry out distance learning (online) with using various kinds of technology. As a student, we can adapt to conditions that inevitabely require students to be able to master technology. There are various types of learning support applications that can be used by students in order to master lecture material well or to fo college assignments. So that during online both students and lecturers are the same (use technology together). Maximum use of technology for lectures can effect student achievement (learning achievement) while online. So this study aims to determine whether or not there is an influence of technology user skills on student learning achievement during online. Research method is quantitative with t test using spss 26 version. So the result of this study indicate that there is a significant influence between student skills in using technology on learning achievement (IP value).Keywords: Technology profiency, learning achievement, online learning, distance learning.